Nietzsche – ekstremalna filozofia języka? - Żukowski, Bartosz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2007)
The coherence of the Nietzschean conception of language is discussed in the article. First, Nietzsche's critique of the referential semantics and the correspondence theory of truth implied by the so-called "tropological" linguistic theory as well as the doctrine of perspectivism is questioned. Consequently, the core of the argumentation is to reveal the naturalistic and metaphysical assumptions of Nietzsche's strict relativistic philosophy of language and interpretation. The conclusiveness of the Nietzschean deconstruction of metaphysics as a pure language creation seems to be doubtful with regard to his construction of the 'will-to-power metaphysics'. Moreover, the reception of the Nietzsche’s philosophy as deconstructivistic after the II World War has to be revised while confronted with his hermeneutical philology. Finally, the status of the Nietzschean affirmation of reality as a play of interpretations in accordance with Paul de Man can be recognized as purely rhetorical.